ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA PADA PERUSAHAAN KECAP WIE SIEN DI KECAMATAN AMPENAN KOTA MATARAM TAHUN 2024 - Suwardi, Didi; Cita, Fitriah Permata; Aprirachman, Rozzy (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
This study aims to see the effect of work experience, working hours, wages, and number of dependents on labor productivity at the Wie Sien soy sauce company in Ampenan District, Mataram City in 2024. Sampling was carried out by probability sampling with a sample size of 32 workers. The analysis tool used in this study to answer the research objectives is multiple linear regression analysis. The results of this study are that the factors that have a partial influence are working hours (X2) and wages (X3). This is because the calculated t value is greater than the t table value, namely working hours (X2) has a calculated t value of (-2.932) and a t table value of (0.007) while wages (X3) has a calculated t value of (4.928) and a t table value of (0.000). while other factors such as work experience and the number of family dependents do not have a partial effect. Because work experience (X1) has a calculated t value of (1.862) and a table t value of (0.073), while the number of dependents has a calculated t value of (1.343) and a table t value of (0.191). Meanwhile, simultaneously, work experience, working hours, wages, and number of dependents have a significant influence on the labor productivity variable.